PHYSICAL ACTIVITIES IN THE 20TH CENTURY ACCORDING TO ERIC HOBSBAWM'S “ERA OF THE EXTREMES” (Fiep Bulletin - online, 2012)
This paper makes an interpretation of Physical Education and Sport in the 20th century from theperspective of the theoretical reference established by the analysis of the English historian Eric Hobsbawm.After a general analysis of Physical Education and Sport, the author attempts to correlate the identifiedfacts with Hobsbawm's historical periods: the Catastrophe Age, The Golden or Development Age (sic) and theCrisis Age, which include the first years of the 21st century.The aspect that is considered most meaningful is related to the Age of the Crisis, when a number oftrends can be identified for the area of Physical Education and Sport. In fact, that is the period when thedeconstructions and reconstructions in this social field take place.
Keywords: physical education; sport; physical activity; Eric Hobsbawm.